Problems associated with the age determination of the oldest pottery yielding cultural layers at the Studenoe 1 site, Transbaikal (southern Siberia). (20th January 2022) - Izuho, Masami; Iizuka, Fumie; Buvit, Ian; Konstantinov, Mikhail V.
Abstracts: Two opinions exist regarding the appearance of the oldest pottery in the Transbaikal Region, Russia— (1) in the early Neolithic during the Holocene Atlantic optimum (6.5–5.5 ka Cal yr BP), or (2) during the Taymir Warm period of the Sartan Glacial (12.0–10.8 ka Cal yr BP)— both derived from the same archaeological component, Cultural Layer 9, at the Studenoe 1 Site. Here we scrutinized data related to the geochronology of early ceramic-yielding layers at Studenoe 1. Results show that the radiocarbon dates between 15, 080 and 12, 720 Cal yr BP contradict site stratigraphy which consists of vertically accreting overbank deposits and buried soil horizons that developed during periods of landscape stability. Palynological and stable-carbon isotope analyses also show inconsistencies with the calibrated radiocarbon dates. We do not yet know the reason for these anomalies, however, it may be that alpine glacier and permafrost thawing, and the subsequent supply of older carbon into the Chikoi River, ceased during cold periods, but accelerated during terminal Pleistocene and early Holocene warm periods, causing a systematic error of older radiocarbon dates.